2015
DOI: 10.4172/2167-0501.1000206
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Mechanisms of Action and Loss of Response to Infliximab in Ibd: A Broader Picture

Abstract: Biologic drugs, as Infliximab (IFX), are widely used in inflammatory bowel disease (IBD). IFX is a chimeric monoclonal immunoglobulin directed against TNF-α and acting in IBD through several mechanisms of action. We divide these mechanisms into central and peripheral. Central mechanisms are considered effective at systemic level, like the reduction of plasmatic pro-inflammatory cytokines (TNF-α, IFN-γ), the promotion of apoptosis of inflammatory cells, the induction of T regulatory cells (FOXP3CD4+) and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(77 reference statements)
0
4
0
2
Order By: Relevance
“…By binding soluble and transmembrane tumor necrosis factor alpha (TNF-a), IFX attenuates inflammation and decreases the need for surgery (2,4,5). However, side effects and nonresponsiveness illuminate the relevance of validating biomarkers to assess therapeutic efficacy (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…By binding soluble and transmembrane tumor necrosis factor alpha (TNF-a), IFX attenuates inflammation and decreases the need for surgery (2,4,5). However, side effects and nonresponsiveness illuminate the relevance of validating biomarkers to assess therapeutic efficacy (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies which have identified elevated BMI and body fat as risk factors for both disease severity and a poorer response to anti-TNF-α treatment, however, the pharmacokinetic mechanisms by which this occurs remain unclear [ 12 , 15 , 22 , 25 ]. This study has confirmed this association by showing a high rate of LOR, of 20% in patients, with a higher BMI and body fat level, and is the is the first to measure the role of post-infusion levels of drug, cytokine or antibodies rather than solely depending on trough levels.…”
Section: Discussionmentioning
confidence: 99%
“…Higher post-infusion IFX levels could be a result of reduced clearance of the drug, caused by a reduced formation of ATIs due to the additional immunosuppressant effect. In addition, Azathioprine is known to cause a reduction in other signalling factors which consume anti-TNF-α, for example other antibodies (anti-nuclear antibodies (ANA) and anti-double stranded DNA (dsDNA), along with other pro-inflammatory cytokines [ 24 , 25 ]. The probability of LOR to the following infusion was shown to be reduced by an increase in post-infusion IFX levels.…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab, the first anti-TNF-α antibody to be FDA (Food and Drugs administration) approved, is a chimeric monoclonal antibody directed against TNF-α, composed of a variable region of murine origin comprising 25%, and a constant region of human origin comprising the remaining 75%, joined through disulfide bonds. Infliximab binds to both soluble and transmembrane forms of TNF-α with high affinity [ 72 ]. It is administered via intravenous infusions at a weight-based dose, and is approved for both induction and maintenance of remission in both CD and UC as published in both the ACCENT I and ACT I trials [ 73 , 74 ].…”
Section: Targeting Pleiotropic Factors Between the Adaptive And Inmentioning
confidence: 99%